Veterinary anthropology: Samples from an emerging field - Broz, Ludek; Keck, Frédéric; Weich, Kerstin (Frontiers in Veterinary Science, 2023)
We contribute to the growing field of veterinary humanities by promoting collaboration between veterinarians and anthropologists. Veterinary anthropology as we propose it analyzes the role of animal diseases in social life while questioning notions of animal health and human health. We distinguish three ways for veterinarians to collaborate with anthropologists, which more or less follow a chronological order. One form of collaboration requires anthropologists to bring risk perception or local knowledge on zoonoses identified by veterinarians. A more recent form of collaboration integrates veterinarians and anthropologists around the view of animals as actors in infrastructures of security. Finally, we suggest that, as veterinary expertise and its roles in contemporary societies is becoming an object of anthropological enquiry, a new space for collaboration is unfolding that enables veterinarians to see themselves through that reflexive lens of anthropological attention. Veterinary anthropology can therefore be defined as an anthropology of veterinarians and with veterinarians.